Factors that can Influence the Motivation of Individual Tax Payment in Medan City - Susan, Susan Grace V Nainggolan; Putri wahyuni,; Ihdina Gustina,; Muammar Rinaldi, (Advances in Social Sciences Research Journal, 2022)
Factors That Can Affect the Motivation of Individual Tax Payment in Medan City. This study aimed to look at the factors that influence the motivation to pay taxes which include Tax Knowledge, Service Quality, and Taxpayer Awareness. The type of data used in this research is quantitative data. Analysis of the data in this study utilized the Multiple Linear Regression Test by transforming the data using the interval successive method (MSI). This study proved that Tax Knowledge, Service Quality, and Taxpayer Awareness spurred public compliance in paying taxes. Therefore, the Tax Service Office can use social media such as Instagram or Facebook accounts to quickly disseminate information about taxation knowledge.